Highly enantioselective catalytic methyl propiolate addition to both aromatic and aliphatic aldehydes. Issue 9 (1st June 2016) - Huang, Jian; Wei, Siping; Wang, Li; Zhang, Chun; Li, Shuangxun; Liu, Pingxian; Du, Xi; Wang, Qin
Graphical abstract: Abstract: The excellent catalytic effect on methyl propiolate addition to a wide range of aromatic and aliphatic aldehydes promoted by inexpensive and commercially available BINOL-based ligand is reported. The catalyst systems showed high yields and excellent enantioselectivities for aromatic aldehydes, and excellent yields and high enantioselectivities for aliphatic aldehydes. Abstract : Methyl 4-hydroxy-4-phenylbut-2-ynoate: C11 H10 O3 [ α ]D 20 = −1.8 ( c 0.950, CH2 Cl2 ) Absolute configuration: not determined Abstract : Methyl 4-hydroxy-4-( o -tolyl)but-2-ynoate: C12 H12 O3 [ α ]D 20 = +10.1 ( c 1.0, CH2 Cl2 ) Absolute configuration: not determined Abstract : Methyl 4-hydroxy-4-( m -tolyl)but-2-ynoate: C12 H12 O3 [ α ]D 20 = −1.7 ( c 0.35, CH2 Cl2 ) Absolute configuration: not determined Abstract : Methyl 4-hydroxy-4-( p -tolyl)but-2-ynoate: C12 H12 O3 [ α ]D 20 = −1.6 ( c 0.985, CH2 Cl2 ) Absolute configuration: not determined Abstract : Methyl 4-(4-( tert -butyl)phenyl)-4-hydroxybut-2-ynoate: C15 H18 O3 [ α ]D 20 = −0.6 ( c 1.13, CH2 Cl2 ) Absolute configuration: not determined Abstract : Methyl 4-hydroxy-4-(2-methoxyphenyl)but-2-ynoate: C12 H12 O4 [ α ]D 20 = −2.1 ( c 1.22, CH2 Cl2 ) Absolute configuration: not determined Abstract : Methyl 4-(2-fluorophenyl)-4-hydroxybut-2-ynoate: C11 H9 FO3 [ α ]D 20 = +8.1 ( c 1.105, CH2 Cl2 ) Absolute configuration: not determined Abstract : Methyl 4-(2-chlorophenyl)-4-hydroxybut-2-ynoate: C11 H9 ClO3 [ α ]D 20 = +35.5 ( c 1.15, CH2 Cl2 ) Absolute configuration: not determined Abstract : Methyl 4-(4-chlorophenyl)-4-hydroxybut-2-ynoate: C11 H9 ClO3 [ α ]D 20 = −2.1 ( c 0.235, CH2 Cl2 ) Absolute configuration: not determined Abstract : Methyl 4-(naphthalen-1-yl)4-hydroxybut-2-ynoate: C15 H12 O3 [ α ]D 20 = +5.2 ( c 1.07, CH2 Cl2 ) Absolute configuration: not determined Abstract : Methyl 4-(furan-2-yl)-4-hydroxybut-2-ynoate: C9 H8 O4 [ α ]D 20 = −3.3 ( c 1, CH2 Cl2 ) Absolute configuration: not determined Abstract : Methyl 4-hydroxy-4-(thiophen-2-yl)but-2-ynoate: C9 H8 O3 S [ α ]D 20 = −22.8 ( c 1.01, CH2 Cl2 ) Absolute configuration: not determined Abstract : Methyl 4-hydroxyhept-2-ynoate: C8 H12 O3 [ α ]D 20 = −4.85 ( c 1.05, CH2 Cl2 ) Absolute configuration: not determined Abstract : Methyl 4-hydroxyoct-2-ynoate: C9 H14 O3 [ α ]D 20 = −2.2 ( c 1.05, CH2 Cl2 ) Absolute configuration: not determined Abstract : Methyl 4-hydroxyundec-2-ynoate: C12 H20 O3 [ α ]D 20 = +1.7 ( c 1.06, CH2 Cl2 ) Absolute configuration: not determined Abstract : Methyl 4-hydroxytridec-2-ynoate: C14 H24 O3 [ α ]D 20 = +1.8 ( c 1.08, CH2 Cl2 ) Absolute configuration: not determined Abstract : Methyl 4-hydroxy-5-methylhex-2-ynoate: C8 H12 O3 [ α ]D 20 = −0.4 ( c 1.03, CH2 Cl2 ) Absolute configuration: not determined Abstract : Methyl 5-ethyl-4-hydroxyhept-2-ynoate: C10 H16 O3 [ α ]D 20 = +3.0 ( c 1.09, CH2 Cl2 ) Absolute configuration: not determined Abstract : Methyl 4-cyclopropyl-4-hydroxybut-2-ynoate: C8 H10 O3 [ α ]D 20 = +35.3 ( c 1.12, CH2 Cl2 ) Absolute configuration: not determined Abstract : Methyl 4-hydroxy-5, 5-dimethylhex-2-ynoate: C9 H14 O3 [ α ]D 20 = −1.0 ( c 1.07, CH2 Cl2 ) Absolute configuration: not determined Abstract : Methyl 4-hydroxy-6-methylhept-2-ynoate: C9 H14 O3 [ α ]D 20 = −8.5 ( c 1.07, CH2 Cl2 ) Absolute configuration: not determined Abstract : Methyl 4-hydroxy-5-phenylpent-2-ynoate: C12 H12 O3 [ α ]D 20 = −0.4 ( c 1.09, CH2 Cl2 ) Absolute configuration: not determined Abstract : ( E )-Methyl 4-hydroxy-6-phenylhex-5-en-2-ynoate: C13 H12 O3 [ α ]D 20 = −1.6 ( c 0.51, CH2 Cl2 ) Absolute configuration: not determined Abstract : ( E )-Methyl 4-hydroxydodec-5-en-2-ynoate: C12 H18 O3 [ α ]D 20 = +40.2 ( c 1.05, CH2 Cl2 ) Absolute configuration: not determined